INFORMATION SECURITY AND PRIVACY AWARENESS IN ONLINE SOCIAL NETWORKS AMONG UTEM UNDERGRADUATE STUDENTS - Othman, Nur Fadzilah; Ahmad, Rabiah; Yusoff, Mariana (Journal of Human Capital Development (JHCD), 2013)
The popularity of online social networks (OSNs) has increased dramatically in the recent years, counting more than one billion users in 2012. Hence, it leads to attraction of huge number of users. Nevertheless, OSNs not only implies a favorable effect on users but also impact an adverse effect on them. User create, administer and deal with the information and because of that, user are also a potential vulnerability. They often willingly, share personal identifying information about them, but do not have a clear idea of who accesses their private information or what portion of it really needs to be accessed. This paper observe the usage purpose and information disclosure in OSNs among undergraduates students in Universiti Technical Malaysia Malacca (UTeM). This paper will also explore level of information security and privacy awareness towards OSNs among them